Preliminary Effectiveness of a Strategy to Promote Healthy Lifestyle Habits in Schoolchildren - Gloria Carvajal-Carrascal; Tania Catalina Chinchilla-Salcedo; César Augusto Niño-Hernández; Paola Sarmiento-González; Angélica María Ospina-Romero; Beatriz Sánchez-Herrera (Children, 2022)
Purpose: To measure the preliminary effectiveness of a strategy to promote healthy lifestyle habits in schoolchildren, aged 6 to 12 years, living in the Andean region of Colombia, 2018–2021. Design and Methods: This is a Nursing Methodological Research, developed in phases: (1) Context and schoolchildren characterization; (2) Strategy design guided by the Whittemore and Grey criteria and the Bronfenbrenner ecological conceptual model; (3) Strategy validation with 11 experts; (4) Trial to evaluate preliminary effectiveness. We applied the strategy in seven different schools with the educational community including 955 schoolchildren between 6 and 12 years of age, 551 parents, 130 teachers and 7 members of the food staff. Results: Our health promotion strategy “Prosalud” has five components: citizenship feeding and nutrition, physical activity, and rest; environment protection, and directing one’s own life. It includes all the participants of the educational community. Conclusions: According to experts, the health promotion strategy “Prosalud” is valid to help promoting healthy lifestyle habits among schoolchildren. This strategy demonstrates its preliminary effectiveness in a group of school children from 6 to 12 years of age, their parents, teachers, and school food staff, in the Andean region of Colombia.